PERANCANGAN UI APLIKASI “PETDOC” BERBASIS MOBILE DENGAN METODE USER CENTERED DESIGN (UCD) - Muhammad Nabil Prayuda; Apriade Voutama (Jurnal Manajamen Informatika Jayakarta, 2025)
The demand for accessible and convenient pet healthcare services is increasing, yet digitalization in this field remains limited compared to human healthcare services. Many pet shops and animal clinics still utilize conventional systems that lack efficiency in their service delivery. This research aims to design a mobile-based user interface (UI) for the PetDoc application using the User Centered Design (UCD) method and the KISS (Keep It Simple, Stupid) principle. The research methodology encompasses four stages: understanding the context of use through interviews with pet shop owners and customers; determining user requirements including online consultations, service reservations, medical records, online store, and articles and tips; designing solutions using Figma application; and evaluating the design with the System Usability Scale (SUS). Evaluation results from five evaluators showed an average SUS score of 88.0 (categorized as "Excellent"), indicating that the PetDoc application UI design has a very good level of usability. This research produced a UI prototype that integrates various main features into a single, easily accessible platform by applying the KISS principle, which simplifies interactions and reduces unnecessary complexity in accessing pet healthcare services.